Lived Spaces of Infant-Toddler Education and Care
XXXI, 244 p. 14 illus.
Keywords: This book conceptualizes the ‘lived spaces’ of infant and toddler early education and care settings by bringing together international authors researching within diverse theoretical frameworks. It highlights diverse ways of understanding the experiences of very young children by exposing the ways that the authors are grappling with the unknown. The work explores broadly the construct and meanings of ‘lived spaces’ as relational spaces, interactional spaces, transitional spaces, curriculum spaces, or pedagogical spaces operating within the social, physical and temporal environment of infant-toddler education settings. The book invites interchange between and among diverse theories and approaches, and through this build new understandings of infants’ and toddlers’ experiences and interactions in early education and care settings. It also considers the implications of this work for policy and practice in infant and toddler education and care. ‘The strength of this manuscript is the international gathering of studies on infants and toddlers in ECEC, where the children are considered active participants and agents in their own lives.’ Camilla Björklund, Department of Education, Communication and Learning, University of Gothenburg, Sweden ‘The strongest aspect of the work is the confidence shown in each chapter. The book is a celebration of expertise from a variety of perspectives. It would be required reading for anyone with a special interest in young children.’ Jane Bone, Faculty of Education, Monash University, Frankston, Victoria, Australia .